Respons Pakchoi (Brassica rapa L.) Akibat Pemberian Beberapa Formula Nutrisi Hidroponik Dan Penggunaan Rockwool Dengan Ukuran Berbeda - Rizka Novi Sesanti; Hilman Hidayat (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2021)
Research on the response of pakchoi (Brassica rapa L.) due to the use of several hydroponic nutrition formulas and the use of different sizes of rockwool aims to (1) compare the growth of pakchoi in four hydroponic nutrient formulas and four rockwool sizes and. (2) compare the results of pakchoi to four hydroponic nutrient formulas and four rockwool sizes. The study used four nutritional formula and four rockwool sizes. Rockwool size used was 2cm3 (r1), 4cm3 (r2), 8cm3 (r3), and 12cm3 (r4), while the nutritional formula used was n1, n2, n3, and n4. Each treatment was applied to the experimental unit according to the split plot design (4x4) with 2 replications. The data obtained will be tested by F test (analysis of variance), and continued with LSD test at α 5% level.The results showed that the use of nutrient 2 (N2) in Pak choi cultivation showed the highest value of plants, the number of leaves, and the best leaf width, respectively 16.55 cm, 8.64 strands, and 114 cm. The use of nutrients 1 (n1) and 2 (n2) in pakchoi cultivation showed wet weight (21.60 g and 23.68 g) and dry weight (5.15 g and 6.58 g) better than n3 and n4. The use of rockwool size 8 cm3 (3) and 12 cm3 (r4) in pak choi cultivation showed the best value on all observation variables except leaf width.